CHROME SPINEL-CLINOPYROXENE PARAGENESIS IN KOMATITES OF THE KOSTOMUKSHA DISTRICT, WESTERN KARELIA - Plakseno A.N.; Gor'kovets V.Ya.; Girnis A.V.; Smol'kin V.F.; Polezhayeva L.I. (My University, 1989)
In the Kostomuksha iron district, located in the Archean granite-greenstone region, komatiites and komatiitic basalts appear among volcanic rocks of the Kontokskaya and the Gimoly groups, as northwest-striking zones. The lack of data on the chemical composition of the minerals in such rocks was the reason for our electron-microprobe investigations of their accessory chrome spinels (the only preserved liquidus phase) and entrapped silicates - sensitive mineral indicators of petrologic processes.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей